A policy window and a network of global and local policy entrepreneurs: The introduction of opioid substitution therapy in Belarus - Babayan Ararat (Sciendo, 2021)
Why does a regime that is predominantly characterised by conservative ideology introduce opioid substitution therapy (OST), a liberal policy? This article applies the Multiple Streams Framework (MSF) to examine the introduction of OST in Belarus. Methodologically, the research draws on qualitative content analysis of drug policy documents and reports as well as on interviews. Results show how an increased HIV prevalence among injecting drug users opened a policy window in the problem stream. The increase in HIV cases could be used by a network of global and local policy entrepreneurs to frame OST as a public health policy instead of a drug policy measure. Findings suggest that, in nondemocratic regimes, global policy entrepreneurs can play a dominant role in introducing new policy ideas. However, the sustainability of the policy change remains questionable when acquiescence by key policymakers is lacking.